244 Does Direct Admission to ICU In Emergency Laparotomy Patients with A NELA Score ≥ 10% Affect Outcome at Fiona Stanley Hospital?. (4th May 2021) - Shepherd, T; Foster, A
Abstract: Introduction: The Australian and New Zealand Emergency Laparotomy Audit (ANZELA) is a quality improvement project based on UK NELA. Direct admission to ICU post-operatively for patients with a NELA ≥ 10% is recommended. In the current pandemic, the use of critical care beds must be rationalised. We investigated if patients with NELA ≥ 10% experienced worse outcomes if admitted to the ward post-operatively (instead of ICU). Method: We performed a retrospective audit of emergency laparotomies at Fiona Stanley Hospital over 6 months December 2019 – May 2020. NELA scores were obtained from the ANZELA database and patient notes reviewed to identify post-operative unplanned ICU admissions and mortalities. Results: Twenty-four (30%) emergency laparotomy patients had a NELA ≥ 10%. Ten (42%) patients were admitted to the ward post-operatively. There were no unplanned ICU admissions in this group. Two (20%) patients had a documented 'code blue' but were managed conservatively on the ward. No patients in this group died within 30 days. Conclusions: Post-operative ward admission in selected patients with NELA ≥ 10% does not result in unplanned ICU admissions or increased mortality at a tertiary Acute Surgical Unit. This data is reassuring as we expect future ICU bed shortages for non-COVID surgical patients during the pandemic.